ANALYSIS OF FACTORS INFLUENCING UMKM TAXPAYER COMPLIANCE IN PEMATANGSIANTAR CITY: ONE-STOP SERVICE TAX PROGRAM APPROACH - Putra, Loist Abdi; Ambarita, Marthin Hutler; Putra, Hendrick Sasimtan; Loist, Christine; Sudirman, Acai (Unitri Press, 2024)
Purpose: This research aims to analyze the factors that influence MSME taxpayer compliance in Pematangsiantar City, with a focus on aspects of tax knowledge, taxpayer awareness, modernization of tax administration, and firmness of tax sanction. Methods: This study employs a quantitative causality method in a literature and field research design. For the purpose of testing hypotheses, a partial least squares-based Structural Equation Model (SEM) technique was used. Findings and discussion: The analysis's findings demonstrate that these four variables significantly and favorably affect taxpayer compliance. A strong understanding of taxes aids in taxpayer comprehension of their responsibilities, and a recognition of the significance of taxes motivates compliance. Stricter tax penalties have a deterrent impact that promotes compliance, while modernized tax administration makes filing and paying taxes easier and more efficient.. Conclusion: This research provides important insights for tax authorities in designing policies and strategies to increase tax compliance among MSMEs, which ultimately contributes to increasing state revenues and regional economic development.